The development of electronic public services in Ukraine - GURZHII, Анна; SHEVCHENKO, Олена (Ius Modernum, 2025)
The implementation of the principle of openness and accessibility of public authorities to citizens has become possible thanks to the course towards introducing e-governance. An important component of this process has been the development of electronic public services as a step towards improving the interaction between the state and the population. Unfortunately, citizens felt positive changes during difficult times for Ukraine – the COVID-19 pandemic, military actions, and the large-scale invasion by enemy. However, these circumstances contributed to the acceleration of mastering new Internet technologies and the implementation of other remote work opportunities, including ways to address public authorities. Moreover, with the development of information technology, the public service sector continues to evolve, which requires new research. The study is based on the hypothesis that electronic public services can become the basis for improving the service of individuals by public authorities, as one of the elements of overcoming corruption in the state, and have prospects for development and enhancement. The study is based on a comprehensive and systematic approach to analysing the prospects for the development of electronic public services. It has been emphasized that there is a rapid development of the specified sector in Ukraine. The integration of information data from various registers has simplified the search process, so the development should continue. Automation in the processes of issuing documents allows for relieving employees, so the work should continue. The removal of a person from the processes of organizing and providing services will help avoid mistakes (due to negligence) and overcome the corrupt component. The implementation of an electronic queue in public institutions ensures the implementation of the principle of fairness and transparency. The number of users of electronic public services is steadily increasing, influenced by the spread of technology among the population. In a difficult time for the Ukrainian people, the "Diia" app has provided an opportunity to exercise the right to appeal, has become a tool for obtaining electronic public services, and continues to improve. The Ministry of Digital Transformation is focusing on artificial intelligence in this area. Each of these areas continues to develop and has prospects for scaling.